Crosstalk between GBM cells and mesenchymal stemlike cells promotes the invasiveness of GBM through the C5a/p38/ZEB1 axis. Issue 10 (17th March 2020) - Lim, Eun-Jung; Kim, Seungmo; Oh, Yoonjee; Suh, Yongjoon; Kaushik, Neha; Lee, Ji-Hyun; Lee, Hae-June; Kim, Min-Jung; Park, Myung-Jin; Kim, Rae-Kwon; Cha, Junghwa; Kim, Se Hoon; et al.
Abstract: Background: Mesenchymal stemlike cells (MSLCs) have been detected in many types of cancer including brain tumors and have received attention as stromal cells in the tumor microenvironment. However, the cellular mechanisms underlying their participation in cancer progression remain largely unexplored. The aim of this study was to determine whether MSLCs have a tumorigenic role in brain tumors. Methods: To figure out molecular and cellular mechanisms in glioma invasion, we have cultured glioma with MSLCs in a co-culture system. Results: Here, we show that MSLCs in human glioblastoma (GBM) secrete complement component C5a, which is known for its role as a complement factor. MSLC-secreted C5a increases expression of zinc finger E-box-binding homeobox 1 (ZEB1) via activation of p38 mitogen-activated protein kinase (MAPK) in GBM cells, thereby enhancing the invasion of GBM cells into parenchymal brain tissue. Conclusion: Our results reveal a mechanism by which MSLCs undergo crosstalk with GBM cells through the C5a/p38 MAPK/ZEB1 signaling loop and act as a booster in GBM progression. Key Points: 1. MSLCs activate p38 MAPK-ZEB1 signaling in GBM cells through C5a in a paracrine manner, thereby boosting the invasiveness of GBM cells in the tumor microenvironment. 2. Neutralizing of C5a could be a potential therapeutic target for GBM by inhibition of mesenchymal phenotype.